Risk Factor Analysis of Diabetes Mellitus Incidence in Pre-Elderly and Elderly Populations in Kedaung Depok - Ruri Firliani Darmadi; Ibnu Malkan Bakhrul Ilmi; Avliya Quratul Marjan (Green Publisher Indonesia, 2025)
Diabetes Mellitus is a medical condition characterized by elevated blood glucose levels. According to the International Diabetes Federation (IDF), Indonesia ranks fifth in the world for the highest number of diabetes cases, with 19.5 million people affected in 2021, and this number is expected to rise to 28.6 million by 2045. In Kedaung Depok Village, the number of diabetes cases in 2023 has also increased compared to the previous year. This study aims to determine the risk factors associated with the occurrence of Diabetes Mellitus in pre-elderly and elderly individuals in Kedaung Depok Village. The study used a cross-sectional design with stratified sampling. Data were collected through questionnaires and analyzed using univariate and bivariate analysis with chi-square tests. The results showed a significant association between family history and the occurrence of diabetes mellitus (p-value=0.029). However, no significant association was found between nutritional status (p-value=0.063) and carbohydrate intake (p-value=0.758) with the occurrence of diabetes mellitus in pre-elderly and elderly individuals in Kedaung Depok Village. In conclusion, family history is the most significant risk factor associated with the occurrence of diabetes mellitus in pre-elderly and elderly individuals in Kedaung Depok Village